Pengaruh pendinginan fluida udara terhadap kinerja fotovoltaik dengan variasi laju aliran udara - Pido, Rifaldo; Boli, Rahmad Hidayat; Rifal, Mohamad; Rauf, Wawan (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2023)
This research aims to evaluate the influence of using air as a coolant on photovoltaic module's power output and electrical efficiency. Fossil energy, as the primary energy source today, has limited supply and presents challenges in meeting future energy demands. In an effort to address this issue, we conducted tests by implementing an air cooling system using a blower at the bottom of the photovoltaic module. The tests were conducted with varying air flow rates, and the results indicate that the use of air cooling can enhance the power output and efficiency of the photovoltaic module. The average power output increased by 31.66 Watts with an efficiency of 3.52%. However, when the air flow rate increased by 1.5 m/s, there was an average power decrease of 28.9 Watts and an efficiency decrease of 3.22%. These findings demonstrate that air velocity affects the temperature, power output, and efficiency of the photovoltaic module.